The Effect Of Leverage On Corporate Values With Profitability As Intervening Variables In Textile And Garment Manufacturing Companies Which Are Listed In Indonesia Stock Exchange (Idx) - Siti Mariam (Universitas Trisakti, 2019)
This study aims to examine and analyze the Effect of Leverage on Firm Value with Profitability as an Intervening Variable in Manufacturing Companies in the Textile and Garment Sector Listed on the Indonesia Stock Exchange (IDX). The sample in this study is the financial statements of manufacturing companies in the textile and garment sector during the period 2015 - 2017 as many as 54 data manufacturing companies in the textile and garment sector are listed on the Indonesia Stock Exchange (IDX). The analysis of this study was carried out using structural equation analysis with the statistical application program SPSS version 23.0 for data processing. The results of this study indicate that leverage has a negative and not significant effect directly on profitability, while leverage has a negative and significant effect directly on firm value and indirectly leverage has a negative and not significant effect on profitability and profitability has a significant effect on firm value.